Far from the Caliph's Gaze: Being Ahmadi Muslim in the Holy City of Qadian - Evans, Nicholas H. A. (Cornell University Press, 2020)
Frontmatter -- Contents -- Preface -- Note on Names and Transliteration -- Introduction: A Troubled Relationship with Truth -- 1. The History of the Ahmadi-Caliph Relationship -- 2. An Enchanting Bureaucracy -- 3. A Failure to Doubt? Polemics and Sectarianism in Qadian -- 4. Prayer Duels to the Death: The Mubahala -- 5. Televising Islam: The Aesthetics of the Caliphate -- Conclusion -- Notes -- Bibliography -- Index